2003
DOI: 10.1002/app.12528
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of polyacrylamide in aqueous solution with interactive additives and cosolvents

Abstract: ABSTRACT:The viscosity of polyacrylamide (PAM) dilute aqueous solutions with NaCl, glucose, and SDS as additives was measured by Ubbelohde viscometry. There was linear relationship between reduced viscosity vs. PAM concentration in aqueous solutions. The Huggins constant k and intrinsic viscosity [] were used to study the conformation of the polymer chains and the degree of polymer-solvent interaction. In addition, the viscosity of diluted PAM solutions in water with acetone, ethanol, DMF, and ethylene glycol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…For instance, at 40 C, the viscosity of P(AM-co-MPAD) solutions is enhanced from 9.2 to 118.3 mPa s when increasing KCl level from 1 to 5%. Nevertheless, when KCl concentration is above 1%, the viscosifying effect seems to be unaffected by KCl concentration when temperature is higher than 60 C. As seen from Figure 7(b), one can find that at lower salinity (<2%) 0 the viscosity of PAM solution decreases with increasing KCl concentration; but at higher salinity, see, above 2%, the viscosity increases with increasing KCl concentration, which is in line with the results reported by Shanks et al, 50 and can be attributed to the competition of salting-out effect of nonpolar section and salting-in effect of amide groups in the PAM molecule.…”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…For instance, at 40 C, the viscosity of P(AM-co-MPAD) solutions is enhanced from 9.2 to 118.3 mPa s when increasing KCl level from 1 to 5%. Nevertheless, when KCl concentration is above 1%, the viscosifying effect seems to be unaffected by KCl concentration when temperature is higher than 60 C. As seen from Figure 7(b), one can find that at lower salinity (<2%) 0 the viscosity of PAM solution decreases with increasing KCl concentration; but at higher salinity, see, above 2%, the viscosity increases with increasing KCl concentration, which is in line with the results reported by Shanks et al, 50 and can be attributed to the competition of salting-out effect of nonpolar section and salting-in effect of amide groups in the PAM molecule.…”
Section: Figuresupporting
confidence: 93%
“…A total of 0.5 mL of 1% (w/v) KPS aqueous solutions was then injected. The polymerization was proceeded at 50 C with a thermostatically controlled water circulating bath under N 2 atmosphere for 10 h. The resulting product was obtained by dropwise addition into fivefold excess of acetone and repeatedly washed with acetone, following with freeze-drying, and 8.15 g of the final product was obtained. For comparison, homopolyacrylamide, PAM, was prepared under the identical conditions.…”
Section: Preparation Of Polymersmentioning
confidence: 99%
“…Previously, the conformation study by the viscosity measurement of PAM diluted water and EG solutions showed that the PAM chains in water was more extended than in EG, which means that a PAM gel should swell more in water than in EG. 17 This solubility and viscosity study provided the same conclusion from a different point of view. The values of ⌬G 121 for acetone, ethanol, and DMF were much smaller than 0, so it can be concluded that the PAM molecules cannot repel each other in these three solvents; there would be no swelling when PAM gel is placed in these three solvents.…”
Section: Solubility Of Pam In Pure Polar Solventssupporting
confidence: 63%
“…Previously, viscosity measurements were used to compare the polymer chain conformations; however, this method did not show the slight differences. 17 Figure 1 also demonstrates that the acetone cosolvents have the smallest polarity compared with the other three cosolvents. Therefore, acetone will be the best precipitant for PAM.…”
Section: Cosolvent Polaritymentioning
confidence: 85%
“…30 Because of the presence of hydrophobes in aqueous solution, the Huggins constant of a modified polymer is expected to be higher than that of its unmodified analogue. However, the trend is reversed here and it is proposed that this is due to the association of the hydrophobic domains.…”
Section: Dilute Solution Viscositymentioning
confidence: 99%